2021
DOI: 10.2337/dc20-2257
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Affects Gut Microbiome Composition and Function and Circulating Short-Chain Fatty Acids: A Randomized Trial

Abstract: OBJECTIVE To determine the longer-term effects of metformin treatment and behavioral weight loss on gut microbiota and short-chain fatty acids (SCFAs). RESEARCH DESIGN AND METHODS We conducted a 3-parallel-arm, randomized trial. We enrolled overweight/obese adults who had been treated for solid tumors but had no ongoing cancer treatment and randomized them ( n = 121) to either 1 ) metformin (up to 2,000 mg), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 46 publications
4
75
0
1
Order By: Relevance
“…Here we identified 152 species, whose abundances were associated with metformin, of which an increased abundance of Escherichia marmotae and E. coli , and decreased abundance of Romboutsia timonensis and Intestinibacter bartlettii were the strongest associations. These top findings are in accordance with earlier studies reporting a significant enrichment of E. coli in the gut microbiota of metformin users 13,40,41 and a decreased abundance in R. timonensis and I. bartletii 13 , as well as with a recent randomized trial that showed that metformin treatment in overweight/obese individuals results in an increased abundance of E. coli and a decreased abundance of I. bartlettii at 6 and 12 months of metformin treatment 42 . Further, an increase of Ruminococcus torques was reported at both time points in that study 42 which is also supported by an earlier study 13 and our study ( p -value = 7.4 × 10 −7 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Here we identified 152 species, whose abundances were associated with metformin, of which an increased abundance of Escherichia marmotae and E. coli , and decreased abundance of Romboutsia timonensis and Intestinibacter bartlettii were the strongest associations. These top findings are in accordance with earlier studies reporting a significant enrichment of E. coli in the gut microbiota of metformin users 13,40,41 and a decreased abundance in R. timonensis and I. bartletii 13 , as well as with a recent randomized trial that showed that metformin treatment in overweight/obese individuals results in an increased abundance of E. coli and a decreased abundance of I. bartlettii at 6 and 12 months of metformin treatment 42 . Further, an increase of Ruminococcus torques was reported at both time points in that study 42 which is also supported by an earlier study 13 and our study ( p -value = 7.4 × 10 −7 ).…”
Section: Resultssupporting
confidence: 92%
“…These top findings are in accordance with earlier studies reporting a significant enrichment of E. coli in the gut microbiota of metformin users 13,40,41 and a decreased abundance in R. timonensis and I. bartletii 13 , as well as with a recent randomized trial that showed that metformin treatment in overweight/obese individuals results in an increased abundance of E. coli and a decreased abundance of I. bartlettii at 6 and 12 months of metformin treatment 42 . Further, an increase of Ruminococcus torques was reported at both time points in that study 42 which is also supported by an earlier study 13 and our study ( p -value = 7.4 × 10 −7 ). R. timonensis is a new species that was recently isolated from the human gut 43 and has not been associated with use of metformin prior to the Mueller et al study 42 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, more research is needed to explore the protective mechanisms of Dubosiella for intestinal inflammation. The relative abundance of Ruminococcus torques group was increased after metformin treatment, which improved overweight/obese adults ( Mueller et al, 2021 ). It means that Ruminococcus torques group could alleviate obesity.…”
Section: Discussionmentioning
confidence: 99%